Duplo papel da proteína MSH2 no reparo de erros de pareamento no DNA e na resposta ao estresse oxidativo em tripanosomatídeos - Viviane Grazielle da Silva (2015)
Different mechanisms are involved in maintaining genomic stability; among them is the DNA Mismatch Repair (MMR). Mainly responsible for the recognition of mismatches and insertion/deletion loops after DNA replication, the main component of MMR is formed by MutS and MutL proteins that are found in prokaryotes and different MutS homologs (MSH) e MutL homologs (MLH), present in eukaryotes. Previous studies aiming to characterize the MMR pathway in the trypanosomatide parasites Trypanosoma cruzi and Trypanosoma brucei provided data suggesting the involvement of these proteins also in the response to DNA oxidative damages. In T. cruzi, sequence analysis of MSH2 from different strains of the parasite showed the existence of three different isoforms of this protein in the parasite population. With the aim of further investigate the role of this protein, we generated lineages of epimastigote forms of T. cruzi with one or both alleles of msh2 gene deleted. Clones with one allele msh2 deleted showed increased susceptibility to hydrogen peroxide (H2O2) treatment, suggesting the involvement of this protein in the response to DNA oxidative damage. Similar results were observed for msh2 knockouts in T. brucei: bloodstream forms with one or two alleles of msh2 deleted showed increased susceptibility to H2O2 when compared to wild type parasites. However, similar to msh2 null mutants generated in the procyclic form of T. brucei, T. cruzi lineages with both msh2 alleles deleted showed increased tolerance to H2O2 treatment when compared to wild type parasites. T. cruzi msh2 null mutants also have increased capacity to survive to intracellular reactive oxygen species generated during macrophages infection. With the aim of evaluating whether MSH2 is involved in the oxidative stress response in a way that is independent of other MMR proteins, T. cruzi single allele msh6 knockouts were also generated. These T. cruzi msh6 mutants were also more susceptible to oxidative stress. A nuclear localization of the two proteins, MSH2 and MSH6, were obtained by fluorescence microscopy analysis of c-myc tag and HA tag or RFP fused to these proteins in transfected parasites. Proteins with the capacity to interact with MSH2 were investigated using parasites expressing TbMSH6 in fusion with a HA tag, and TbMSH2 expressed with a myc tag. Co-immunoprecipitation assays with parasites expressing the tagged proteins showed that T. brucei MSH2 interacts with MSH3 and MSH6, as expected, but no additional interactions were observed even after treatment with genotoxic agents such as MNNG and H2O2. Taken together our results lead us to formulate the hypothesis that the deletion of two alleles of msh2 in epimastigote form of T. cruzi and procyclic form of T. brucei has a strong impact on the capacity of these parasites to resist to the oxidative stress generated by its essentially aerobic metabolism. Differences in the phenotype of msh2 mutants observed in the bloodstream form of T. brucei could be explained by metabolic differences, since this form, in contrast to procyclic forms, has an anaerobic metabolism, which generate less ROS. The hypothesis that procyclic msh2 mutants had to adapt to survive in the absence of MSH2 was corroborated by the comparative analysis of global genic expression that showed a reduced expression of the enzyme NADH-dependent fumarate reductase in the mutants compared to WT parasites, an enzyme involved in ROS generation.